The Reconstruction of The Authorityof The Indonesian Waqf Board (BWI) in Relation to The Supervision of Waqf Assets - Huzaimah Al Anshori (Hukum dan Masyarakat Madani, 2026)
Supervision of waqf property is essential to ensure its protection, sustainability, and utilization for the public benefit. In this context, the Indonesian Waqf Board (BWI) plays a strategic role in safeguarding both movable and immovable waqf property from disputes, misuse, and claims for repossession by the waqif's heirs. This study aims to analyze the current legal framework governing the authority of BWI and to reconstruct its supervisory authority for future implementation. This research employs a normative legal research method using statutory, case, and conceptual approaches. The data consist of primary and secondary legal materials collected through library and document studies and analyzed qualitatively. The findings indicate that BWI is authorized to supervise and develop nazhir, dismiss and replace nazhir, approve changes in the designation and legal status of waqf property, authorize the exchange of waqf property, manage and develop waqf assets at the national and international levels, and provide recommendations and considerations to the government in formulating waqf policies. This study further proposes a reconstruction of the supervisory authority of BWI through the establishment of BWI offices at the sub-district level within the Office of Religious Affairs (KUA) to strengthen the supervision of both movable and immovable waqf property, thereby enhancing legal protection and ensuring more effective and optimal waqf governance. Abstrakuntuk menjamin perlindungan, keberlanjutan, dan pemanfaatannya bagi kemaslahatan masyarakat. Dalam konteks tersebut, Badan Wakaf Indonesia (BWI) memiliki peran strategis dalam memastikan harta benda wakaf, baik bergerak maupun tidak bergerak, terlindungi dari sengketa, penyalahgunaan, maupun penarikan kembali oleh ahli waris wakif. Penelitian ini bertujuan untuk menganalisis pengaturan kewenangan BWI berdasarkan ketentuan hukum yang berlaku saat ini serta merekonstruksi pengaturan kewenangan pengawasannya pada masa yang akan datang. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual. Sumber data yang digunakan meliputi bahan hukum primer dan bahan hukum sekunder yang dikumpulkan melalui studi kepustakaan dan studi dokumen, kemudian dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa kewenangan BWI meliputi pembinaan nazhir, pemberhentian dan penggantian nazhir, pemberian persetujuan dan/atau izin atas perubahan peruntukan dan status harta benda wakaf, pemberian persetujuan atas penukaran harta benda wakaf, pengelolaan dan pengembangan harta benda wakaf berskala nasional dan internasional, serta pemberian saran dan pertimbangan kepada pemerintah dalam penyusunan kebijakan di bidang perwakafan. Penelitian ini juga menawarkan rekonstruksi pengaturan kewenangan pengawasan melalui pembentukan BWI di tingkat kecamatan yang berkedudukan pada Kantor Urusan Agama (KUA) guna memperkuat pengawasan terhadap harta benda wakaf, baik bergerak maupun tidak bergerak, sehingga tercipta perlindungan hukum yang lebih efektif dan optimal.
Keywords: Authority Reconstruction; Indonesian Waqf Board (BWI); Waqf Asset Supervision